2023
DOI: 10.1039/d3tc01901b
|View full text |Cite
|
Sign up to set email alerts
|

Cesium–lead–halide perovskite triggered visual platform: a disposable paper-based nano-temperature sensor for cold chain transport

Abstract: Transportation and storage of primary agricultural products, processed foods, and special items should be carried out in accordance with the requirements of cold chain transport to ensure that they are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Cui et al reported a fluorescent temperature sensor with multiple color change patterns based on the fluorescent wavelength-shift triggered by the anion-exchange reaction between Br – and I – . The proposed fluorescent demonstrated portability and stability in multiple threshold temperatures from −68 to 4 °C during the food clod chain transportation . Besides, perovskite nanocrystals have been utilized to detect foodborne pathogens in the water.…”
Section: Applications In Food Productsmentioning
confidence: 99%
“…Cui et al reported a fluorescent temperature sensor with multiple color change patterns based on the fluorescent wavelength-shift triggered by the anion-exchange reaction between Br – and I – . The proposed fluorescent demonstrated portability and stability in multiple threshold temperatures from −68 to 4 °C during the food clod chain transportation . Besides, perovskite nanocrystals have been utilized to detect foodborne pathogens in the water.…”
Section: Applications In Food Productsmentioning
confidence: 99%
“…Sustainable materials have been used in some applications, and wide ranges of temperatures can be achieved. Cui (2023) developed a nano-temperature sensor based on paper for cold chain storage with multiple temperature thresholds from −68 • C to 4 • C [23]. Apart from temperature indicators, data loggers are often used to keep track of the temperature and humidity data.…”
Section: Literature Reviewmentioning
confidence: 99%